THU0374 Articular symptoms in cryopyrin-associated periodic syndrome: A retrospective french study. (23rd January 2014) - Houx, L.; Guennoc, X.; Hachulla, E.; Koné-Paut, I.; Quartier, P.; Grateau, G.; Pillet, P.; Hamidou, M.; Lemelle, I.; Pagnier, A.; Neven, B.; Richez, C.; et al.
Abstract : Background: The cryopyrin-associated periodic syndrome (CAPS) is a rare inherited inflammatory disease associated with mutations in NLRP3 .It includes disorders of increasing severity, including the familial cold autoinflammatory syndrome (FCAS), the Muckle–Wells syndrome (MW), and neonatal-onset multisystem inflammatory disorder (NOMID) (also known as he chronic infantile neurologic, cutaneous, and articular syndrome: CINCA).Articular symptoms are frequently described in CAPS but their frequency have been poorly investigated. Objectives: Our objectives were to describe the type and frequency of articular symptoms in a cohort of CAPS patients follwed in adults or paediatricien departments in France. Methods: We conducted a retrospective study concerning articular manifestations (joint, bone and muscle symptoms) in patients with CAPS. Paediatricians, internal medicine and rheumatologists were contacted. Medical data were collected using standardized questionnary and radiographs if available were analysed. Results: 75 patients were included, (12 FCAS, 45 MW, 12 CINCA/NOMID and 6 unclassified. 53% were females (40/75).Among them, 47 are adults (mean age: 31.8±15 years) and 28 are children (11±4.5 years). Disease onset was 4.7±2 years, however the age at the diagnosis was 18±4.5 years. The first symptoms were more frequently cutaneous (61%), fever (20%) articular (17%) and neurological (10%). 56 (74%) had a familial history of CAPS. 9 (12%) patients had CAPS without mutation. During the follow-up, only 17 (23%) did not have articular symptoms. For the remaining 55 (75%) had arthralgia and 46 (60%) had synovitis. The more affected joints were respectively the ankles (66%), knees (45%), hips (33%), feet (25%) and hands (21%). Only one patient with CINCA/NOMID had typical arthropathy with bone abnormalities enlarged, deformed femora and patellae. These arthragia were considered as predominant for 20% of the patients Radiographs were rarely performed. Tendinopathies occured in 12 (16%) of the patients and myalgia in 26 (35%). Conclusions: Articular symptoms are frequent in patients with CAPS and considered as invalidating in 20% but they are poorly investigated by radiographs. Bone deformities are rare. Arthralgia can affected hand and feet. Disclosure of Interest: None Declared